Supertrends : 50 things you need to know about the future - Tvede, Lars, 1957- (John Wiley & Sons, 2020)
"Supertrends In Technology: 50 Things You Need to Know About the Future is about how efficient futurists work, and how we can expect the world to evolve in terms of demographics, general economics, technologies, business models, resources, environment and lifestyles. This book addresses how to predict the future, what we can expect from it, and how companies and government should adapt to the accelerating change, and will also: Explain the core principles of efficient forecasting . List a number of underlying drivers and recurring social patterns which help explain and predict events. Shows how companies and governments can become more future-proof by adopting new and innovative management principles. Introduce new technologies and how they will be applied. The Supertrends project is a joint venture between Lars Tvede and Trifork. Trifork makes approx. 50 technology seminars annually, which are attended by an average of 1,500 delegates each. The Supertrends tools will be incorporated onto the seminars. The forthcoming www.supertrends.com site, app and community will initially have 10,000 selected expert members who will each contribute to the future consensus timeline, and will continue to be expanded. The author's Futures Institute will conduct workshops, speeches and seminars for leaders and investors. They will include books in these. Lars Tvede also speaks on the future at approx 50 events per annum - (average size approx. 150 people). Includes a session with 300 top managers of Novo, 30 from McKinsey, 500 at Danish Growth Fund Annual meeting, 150 at Danish parliament, etc. These events were for companies, think tanks, political parties and universities"--